Parturition in buffaloes - SINGH, RAGHUBIR; KHAR, S K; CHANDER, SURESH (The Indian Journal of Animal Sciences, 2013)
The duration and sequence of events of different stages of parturition in buffaloes have been described on the basis of observation on 10 parturient buffaloes. The first, second and third stages of parturition required, on an average, 281.75,78.50 and 268.40min, respectively. Four animals expelled the amniotic sac as the first water bag in place of the chorioallantoic membranes. The probable significance of the findings are discussed.